A Case of Congenital Prepapillary Vascular Loop: A Rare Anomaly - Mohammed, Neha; Sharma, Aakanksha; Mohammad, Irshan (Asian Journal of Medical Research, 2023)
Congenital vascular anomalies are a rare occurrence and most of time an accidental finding in a patient coming for fundus examination. Prepapillary vascular loop is a type of congenital vascular anomaly. Though most of cases are asymptomatic, regular follow up is of paramount importance for timely diagnosis of complications if any.